Upaya Pemerintah Brazil Mengatasi Deforestasi Hutan Hujan Amazon Pada Era Luiz Inacio Lula Da Silva - Requela Hutapea; Frentika Retnowatik (Politeia: Jurnal Ilmu Politik, 2026)
Deforestation of the Amazon Rainforest is caused by agribusiness expansion, illegal mining, and weak law enforcement. This research analyzes President Lula da Silva's efforts to combat deforestation in Brazil's Amazon Rainforest during the 2023-2024 period. Using descriptive in nature and uses secondary data. The data analysis technique used is qualitative, employing O'Neill's Environmentalism theory. The results of this research found that Lula da Silva's third term (2023-2024) prioritized controlling deforestation. At the domestic level, Lula da Silva's efforts included the reactivation of the fifth phase of the PPCDAm with market incentives, the appointment of Marina Silva as Minister of the Environment, and the strengthening of the capacity of IBAMA and ICMBio through increased budgets, personnel, and forest fire management programs. Brazil's efforts at the international level reaffirm the 2030 zero deforestation target in line with the Paris Agreement and lead the 2023 Amazon Conference, which resulted in the Belém Declaration. This policy has had a tangible impact, reducing deforestation by nearly 50% in 2023 compared to 2022, followed by a further decline of 30.6% between August 2023 and July 2024, demonstrating that domestic efforts and environmental diplomacy are working effectively together.